2017
DOI: 10.1371/journal.pone.0172591
|View full text |Cite
|
Sign up to set email alerts
|

A pan-European epidemiological study reveals honey bee colony survival depends on beekeeper education and disease control

Abstract: Reports of honey bee population decline has spurred many national efforts to understand the extent of the problem and to identify causative or associated factors. However, our collective understanding of the factors has been hampered by a lack of joined up trans-national effort. Moreover, the impacts of beekeeper knowledge and beekeeping management practices have often been overlooked, despite honey bees being a managed pollinator. Here, we established a standardised active monitoring network for 5 798 apiarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 30 publications
9
138
1
2
Order By: Relevance
“…) and the EPILOBEE consortium (Jacques et al . ) – programs that were developed in the US and Europe, respectively (for more details see WebPanel 2). We adapted the questions to account for differences in Northern and Southern Hemisphere seasonal phenology, types of diseases, and botanical origins of honey (in order to make the questionnaire more compatible with South American biogeographic conditions), and prepared a Spanish translation.…”
Section: Methodsmentioning
confidence: 99%
“…) and the EPILOBEE consortium (Jacques et al . ) – programs that were developed in the US and Europe, respectively (for more details see WebPanel 2). We adapted the questions to account for differences in Northern and Southern Hemisphere seasonal phenology, types of diseases, and botanical origins of honey (in order to make the questionnaire more compatible with South American biogeographic conditions), and prepared a Spanish translation.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decades, managed honey bees faced a widespread decline in Europe as reported in large national and European bee monitoring projects (Genersch et al, 2010;Jacques et al, 2016Jacques et al, , 2017Odoux et al, 2014;Porrini et al, 2016;van Der Zee et al, 2014). The causes that influence honey bee colony health are multiple (Goulson et al, 2015;) and may be subdivided into 5 categories: (1) chemical exposure (Böhme et al, 2017); (2) diseases and biological agents (Higes et al, 2009); (3) change in land use and landscape fragmentation ; (4) climate change and variability ; (5) beekeeping practices (Jacques et al, 2017).…”
Section: Honey Bee Healthmentioning
confidence: 99%
“…The causes that influence honey bee colony health are multiple (Goulson et al, 2015;) and may be subdivided into 5 categories: (1) chemical exposure (Böhme et al, 2017); (2) diseases and biological agents (Higes et al, 2009); (3) change in land use and landscape fragmentation ; (4) climate change and variability ; (5) beekeeping practices (Jacques et al, 2017).…”
Section: Honey Bee Healthmentioning
confidence: 99%
“…The authors found that colony loss was highly variable across the 17 countries surveyed. Over the two-year study period, annual losses ranged from 2.6-36% and it was observed that high summer loss were associated with high winter loss (Laurent et al 2016, Jacques et al 2017. In 2014-2015, Seitz et al (2016) reported annual honey bee mortality rates to range from 14-63% across the United States.…”
Section: Honey Bee Declinementioning
confidence: 99%